Post-Retirement Engagement Plan Among Oil Company Workers in the Niger Delta Region of Nigeria: Is there Interest in Agricultural Investment? (Global Journal of Human-Social Science, 2016)
Workers, including oil company workers are advised to plan for their exit from their employing firms or establishments to avoid been driven below poverty line after retirement. There is also advocacy for people to invest in agriculture by state and federal governments. This study therefore examined the level of interest in agricultural investment among oil company workers in the Niger Delta Region of Nigeria, in their post-retirement engagement plans. From among the workers in the oil companies operating in the study area, 232 respondents were selected and data were elicited from them with the use of questionnaire. The data were treated with the application of descriptive statistics and Pearson's Product Moment Correlation (PPMC) analysis. The level of interest in agricultural investment among the oil company workers is low (31.03%) just as most of them had 11-15 years left to be in service and most (68.53%) of them planned to remain in urban settlements after retirement.
Keywords: post-retirement engagement; agriculture; plantation agriculture; fish farming; poultry farming; return migration; rural settlement